Identity sociological perspectives - Lawler, Steph 1958- (Polity Press, 2014)
Lawler examines debates surrounding identity, and shows how identity is part of the fabric of society, and integral to social relations. The book includes all the core topics covered by courses in this field and uses rich and varied contemporary empirical examples to illustrate the discussion.